Design and Processing of Alumina Plate Composites for Ballistic Nacre Alumina Structures. (2nd January 2018) - Haynes, A.; Reinhardt, L.; Lim, C.
ABSTRACT: Nacre is a hierarchical multi-composite matrix consisting of mineral plate-like structures stacked up similar to brick and mortar. When impacted with a projectile this type of structure is expected to reduce the overall shock loading into the system as well as projectile velocity as a consequence of variations in structural stiffness between the composite plates and the organic interlayers. Bio-mimicked nacre derived from alumina as the base ceramic is also shown to have increased fracture toughness over an alumina monolith. One challenge to building the nacre alumina structure is the design and processing of the composite mineral plates which should be comprised of roughly 90-95% nano-filler and 5-10% organic binder. In order for these plates to accurately mimic the nacre mineral plates they must also emulate aspect ratios on the order of 1:10 to 1:20. This paper will discuss the design and processing of nacre-alumina plates for studies into the impact behavior of nacre composites.